Environmental Activism: Pro-Environmental Behavior, Consumerism, and Environmental Justice (University of Denver Undergraduate Research Journal, 2023)
This literature review examines established research on the concept of pro-environmental behaviors (PEB) and its subsects: activism and consumerism. There are competing opinions regarding the salience of pro-environmental activist behavior. This dichotomy is characterized by the role of social media, which can be simultaneously used for performative identity signaling and as a platform to facilitate global collective activism. The research shows a stark contrast between pro-environmental activism and pro-environmental consumerism, with the former acknowledging historical injustices and addressing the social, economic, and environmental disparities created by neo-liberal policies designed with the purpose of profit extraction at the expense of marginalized communities. This review concludes with a question not addressed in current research: does pro-environmental consumerist behavior create a sense of complacency that hinders the necessary actions for systemic change? This is important to consider going forward as corporations continue to lead consumers to believe their products and practices are sustainable, perpetuating the neoliberal conservation narrative that fundamentally prioritizes capitalism over systemic environmental change.